THE INFLUENCE OF QUALITY OF HUMAN RESOURCES AND COMMUNICATION ON THE PERFORMANCE OF CIVIL SERVANTS IN THE REGIONAL SECRETARIAT OF DHARMASRAYA REGENCY WITH ORGANIZATIONAL COMMITMENT AS INTERVENING VARIABLES - Meldi, Meldi; Heryanto, Heryanto (Archives of Business Research, 2019)
This study attempts to examine the effect of the quality of Human Resources (HR) and communication on the performance of Civil Servants in the Regional Secretariat of the Regency of Dharmasraya with organizational commitment as an intervening variable. This study uses descriptive quantitative methods. The study population consisted of 60 people from employees. To obtain a valid and realistic instrument, the validity and reliability test, normality test, multicollinearity test and heterocedasticity test were tested. The data analysis technique used is path analysis. The results showed that indirectly the quality of human resources through commitment was not able to provide a significant positive effect on performance. This means that the existence of a commitment is needed to increase the influence of the environment on employee performance at the Dharmasraya Regency Regional Secretariat. Therefore commitment is needed to increase the influence of communication on employee performance at the Regional Secretariat of the Regency of Dharmasraya The empirical findings indicate that to improve Community Satisfaction, the Regional Secretariat of the Dharmasraya Regency needs to pay attention and focus more on the quality of human resources through a commitment to improve performance.